Dural arteriovenous fistula arising after intracranial surgery in posterior fossa of nondominant sinus: Two cases and literature review - Yokoyama, Shohei; Nakagawa, Ichiro; Kotsugi, Masashi; Wajima, Daisuke; Wada, Takeshi; Kichikawa, Kimihiko; Nakase, Hiroyuki (Asian Journal of Neurosurgery, 2019)
The results of recent clinical and experimental studies suggest that the most important factor associated with the pathogenesis of dural arteriovenous fistula (AVF) is sinus thrombosis and subsequent venous or intrasinus hypertension. Here, we describe two patients who each developed a dural AVF after a posterior fossa craniotomy on the side of the nondominant or hypoplastic transverse (TS)-sigmoid (SS) sinuses. A 63-year-old female underwent surgical resection of a meningioma in the left cerebellopontine angle. Preoperative subtraction digital angiography (DSA) revealed a hypoplastic, ipsilateral left TS-SS and the sinus occlusion was revealed after surgery. Sixteen months later, she presented with a progressive left retroauricular, pulse-synchronous bruit. An AVF in the left TS-SS region was diagnosed by DSA and treated with transvenous coil embolization. The patient recovered without neurological deterioration. A 56-year-old female underwent surgical removal of an epidermoid tumor in the right cerebellopontine angle. Preoperative DSA revealed severe, ipsilateral right TS stenosis and the sinus occlusion was revealed after surgery. Two years later, she presented with the progressive right retroauricular, pulse-synchronous bruit, which was diagnosed by DSA as dural AVF in the right TS-SS region. She was treated with transvenous coil embolization and recovered without neurological deterioration. Sinus manipulation during intracranial surgery carries a potential risk of dural AVF development and this should be carefully considered, even when the ipsilateral TS-SS is nondominant or appears hypoplastic.
Keywords: Development hypoplastic sinus; dural arteriovenous fistulae; postoperative outcome